In vitro efficacy of the essential oil of Piper cubeba L. (Piperaceae) against Schistosoma mansoni - Magalhaes, Lizandra G.; de Souza, Julia M.; Wakabayashi, Kamila A. L.; Laurentiz, Rosangela da S. [UNESP]; Vinholis, Adriana H. C.; Rezende, Karen C. S.; Simaro, Guilherme V.; Bastos, Jairo K.; Rodrigues, Vanderlei; Esperandim, Viviane R.; Ferreira, Daniele S.; Crotti, Antonio E. M.; et al. (Springer, 2012)
In this paper, cercariae, schistosomula, and adult Schistosoma mansoni worms were incubated in vitro with the essential oil of Piper cubeba (PC-EO) at concentrations from 12.5 to 200 mu g/mL, and the viability was evaluated using an inverted microscopy. The effects of PC-EO at 100 and 200 mu g/mL on the stages of S. mansoni were similar to those of the positive control (PZQ at 12.5 mu g/mL), with total absence of mobility after 120 h. However, at concentrations from 12.5 to 50 mu g/mL, PC-EO caused a reduction in the viability of cercariae and schistosomula when compared with the negative control groups (RPMI 1640 or dechlorinated water) or (RPMI 1640 + 0.1% DMSO or dechlorinated water + 0.1% DMSO). on the other hand, adult S. mansoni worms remained normally active when incubated with PC-EO at concentrations of 12.5 and 25 mu g/mL, and their viabilities were similar to those of the negative control groups. In addition, at concentrations ranging from 50 to 200 mu g/mL, separation of all the coupled adult worms was observed after 24 h of incubation, which is related to the fact of the reduction in egg production at this concentration. The main chemical constituents of PC-EO were identified by gas chromatography-mass spectrometry as being sabinene (19.99%), eucalyptol (11.87%), 4-terpineol (6.36%), beta-pinene (5.81%), camphor (5.61%), and delta-3-carene (5.34%). The cytotoxicity of the PC-EO was determined, and a significant cytotoxicity was only obtained in the concentration of 200 mu g/mL after 24 h treatment. The results suggest that PC-EO possesses an effect against cercariae, schistosomula, and adult worms of the S. mansoni.